Electrophysiological effects of mexiletine in man. - Roos, J C (1976)
The electrophysiological effects of intravenous mexiletine in a dose of 200 to 250 mg given over 5 minutes, followed by continuous infusion of 60 to 90 mg per hour, were studied in 5 patients with normal conduction and in 20 patients with a variety of disturbances of impulse formation and conduction, by means of His bundle electrography, atrial pacing, and the extrastimulus method. In all but 2 patients the plasma level was above the lower therapeutic limit. Mexiletine had no consistent effects on sinus frequency and atrial refractoriness. The sinoatrial recovery time changed inconsistently in both directions; however, of the 5 patients in whom an increase was evident, 3 had sinus node dysfunction. In most patients mexiletine increased the AV nodal conduction time at paced atrial rates and shifted the Wenckebach point to a lower atrial rate. The effective refractory period of the AV node was not consistently influenced, while the functional refractory period increased in 12 out of 14 patients. The HV intervals increased by a mean of 11 ms in 8 patients and were unchanged in 17. Both the relative and effective refractory period of the His-Purkinje system increased after mexiletine. Non-cardiac side effects occurred in 7 out of 25 patients, and cardiac side effects, including one serious, in 2. The results indicate that mexiletine shares some electrophysiological properties with procainamide and quinidine, when given to patients with conduction defects, and that the drug should not be used in patients with pre-existing impairment of impulse formation or conduction. It has additional effects on AV nodal conduction which may be of value in the treatment of re-entrant tachycardias involving the AV node.